Estudo do comportamento de um tirante em argila mole - Ehrlich, Maurício (1978)
This dissertation is on the reological behavior of anchors in soft clay, including analyses of load capacity, sensitivity at rupture, stress-displacement characteristics and the influence on them of the elongability of the anchor-bulb. A mathematical expression for the shear stress distribution along anchor bulbs was developed, an index representative of the elongability of anchors being established. By means of field load test, load-capacity, stress-strain characteristics and sensitivity at rupture of anchors in soft clay were determined. The influence of time was assessed by means of creep tests. The field test were analyzed with the aid of laboratory shear strength and creep tests on undisturbed soil samples. The influence of the elongability of the bulb on the load capacity and the stress-displacement-time behavior of anchors were theoretically analyzed and comparisons with experimental results were made. The field creep tests were also analyzed according to the Brazilian Standard ABNT, P-NB-565.